ANALISIS KENYAMANAN SUHU RUANG - Allif Silfiyana Rohman; Upik Nurbaiti; Fianti Fianti (Universitas Lambung Mangkurat, 2021)
Global warming causes the earth's temperature to increase, making humans reduce outdoor activities and spend a lot of time indoors. Temperature that is too hot or cold cause discomfort to the users of the room. Based on the description of the problem, the researcher will analyze the thermal comfort of the room. The method used in this research is a survey using the Hygrometer Thermometer HTC-2 to obtain data on indoor and outdoor temperature and humidity at certain times. This study took data using the Hygrometer Thermometer HTC-2 four times in one day. The results showed that room temperature comfort was obtained at a temperature range of 27 °C to 29 °C. Then the comfort level is based on the highest time at 06.00 - 09.00 WIB with an average temperature at that time of 27.75 °C.